Sustainable Development Idea in Laudato Si’ Encyclical - Pawłowski, Artur (Studia Ecologiae et Bioethicae, 2017)
The Laudato Si’ encyclical is the most important document of the Catholic Church in recent years. Discussing the problem of endangered proper development of human society, Pope Francis refers to the idea of sustainable and integral development, showing the link between environmental problems and general issues, economic and social. He emphasizes the importance of the growing gap between the rich and the poor, calling for respect towards the basic needs and rights of the whole human family. The Pope advocates rejection of exclusive globalization, arguing that this change is possible – for the common good of us all.